Impact of cadmium exposure during pregnancy on hepatic glucocorticoid receptor methylation and expression in rat fetus. - Paula Castillo (Public Library of Science (PLoS), 2012)
Adverse fetal environment due to maternal undernutrition or exposure to environmental chemicals alters glucocorticoid (GC) metabolism increasing the risk of metabolic disorders in adulthood. In this study, we investigated the effects of maternal exposure to cadmium (Cd, 50 ppm) during pregnancy in the methylation of fetal hepatic glucocorticoid receptor promoter (GR) and the correlation with its expression and that of the DNA methyltransferases (DNMT1a and 3a). We also studied the expression of liver phosphoenolpyruvate carboxykinase (PEPCK) and acyl-CoA oxidase (AOX), two enzymes involved in the metabolism of carbohydrates and lipids respectively. The methylation of the rat GR gene exon 1(10) (GR1(10)) in nucleotides -2536 to -2361 was analyzed by pyrosequencing. Quantitative real time PCR was used to assess hepatic GR, PEPCK and AOX mRNA, and their protein levels using Western blotting analysis. Differential methylation was noted across groups at all CpG sites in the GR exon 1(10) in a sex-dependent manner. In males, CpG were more methylated than the controls (185 ± 21%, p<0.001) but only CpG sites 1,6,7 and 9 showed a significantly different extent of methylation. In addition, a lower expression of GR (mRNA and protein) was found. On the contrary, in females, CpG were less methylated than the controls (62 ± 11%, p<0.05) and overexpressed, affecting PEPCK and AOX expression, which did not change in males. The GR methylation profile correlates with DNMT3a expression which may explain epigenetic sex-dependent changes on GR1(10) promoter induced by Cd treatment. In conclusion, Cd exposure during pregnancy affects fetal liver DNMT3a resulting in sex-dependent changes in methylation and expression of GR1(10). Although these effects do not seem to be directly involved in the low birth weight and height, they may have relevant implications for long-term health.